“The Human Side of Enterprise” Components of Contemporary Business Management - Krauss, Yaron (Marketing & Menedzsment, 2019)
The technological innovations and the electronic revolution of the last two decades have made business management in this information-rich world a unique challenge (Simon 1997). For more conservative industries such as banks, the transformations described by Crone (1995) - a shift from paper to electronics and a shift from branches to e-banking - constitute a considerable problem. Moreover, as new agents entered the intermediation market and the processing services, a drastic erosion in the banks market share have been witnessed, from 75% in 1950 to less than 30% in the mid-90s. But not only banks need to adjust to the new economic reality.